Preparation and isolation of the cellulose nanocrystals from banana leaves by chemical treatments - Nguyen, Dinh Hung; Nguyen, Van Quy; Nguyen, Vinh Tien; Nguyen, Vu Viet Linh (Vietnam Journal of Science and Technology, 2024)
Many banana leaves and other residues from banana trees were discharged as waste annually. This biomass resource could isolate negatively charged and large surface banana cellulose nanocrystals (BA-CNCs). However, very few studies investigate the isolation process and the applications of BA-CNCs. Therefore, in this study, we proposed a procedure for isolating BA-CNCs from banana leaf waste relying on sequential chemical treatments including alkali‒, bleaching−, and acid hydrolysis processes, respectively. After each chemical treatment stage, the changes in morphology, size, chemical composition, and crystalline structure of banana fibers were analyzed by scanning electron microscopy (SEM), dynamic light scattering (DLS), Fourier-transform infrared spectroscopy (FT-IR), and X-ray diffraction (XRD) methods, respectively. Noticeably, the SEM images showed that these isolated BA-CNCs had a uniform rod-shaped morphology. The DLS and zeta potential analyses revealed that these CNCs possess an average hydrodynamic size of 373.1 ± 48.15 nm and a surface charge of -32.28 mV, respectively. These nanosized and moderate negative charged CNCs potentiate their applications for various purposes, such as fabrications of composite films, and sorbents for wastewater treatment.